The Application of Al-Qahtani Method for Dental Age Estimation of Down Syndrome Children - Tridiyanti, Frita Rahima; Apriyono, Dwi Kartika; Barid, Izzata (Jurnal Kesehatan, 2024)
Dental age estimation is one of the methods in the forensic dental examination. Dental age estimates are often carried out to complete the victim's identity using methods from experts such as Al-Qahtani. There have been many studies related to estimating tooth age using the Al-Qahtani method in normal humans but not in human subjects with special needs, such as children with down syndrome. This study aims to determine the estimated dental age using the Al-Qahtani method in children with down syndrome and to differentiate between chronological age and dental age in children with down syndrome. This research is a cross-sectional study. The research subjects were 13 children with down syndrome who attended special schools in the Jember Regency and met the sample criteria. Tooth age estimation is done by matching the results of panoramic radiographs with the Al-Qahtani Atlas. Data were analyzed using Shapiro-Wilk, Levene's Test, and paired sample T-Test. Estimating dental age using the Al-Qahtani method shows varying dental age values, and there is a delay in the dental age of boys compared to girls with down syndrome. The dental age of all research subjects was delayed from their chronological age. The dental age of children with Down syndrome estimated using the Al-Qahtani method shows an average value of 1 year 2.5 months, and there is a difference between dental age and chronological age with a difference of 1 year seven months. Therefore, adjustments need to be made if the Al-Qahtani method is applied to children with down syndrome.